Memahami Pengalaman Anak Punk Kota Semarang Dalam Penggunaan Simbol-Simbol Komunitasnya - Aji Nurkafi, Fabi; Hasfi, Nurul; Nugroho, Adi (Interaksi Online, 2024)
This research is based on the existence of Semarang City Punk Community which actively displays symbols in their events by members of the Punk Community. This study aims to analyze the formation of symbols and also the experience of members of the punk community in using their symbols. This research was conducted qualitatively with a phenomenological approach. The data used in this study were data from in-depth interviews with a number of informants. The informants in this study had the criterion of being members of the punk community who actively used punk community symbols. Analysis in this research will be carried out using Social Identity Theory, Identity Communication Theory, and Symbolic Interaction Theory. With a phenomenological approach with Interpretative Phenomenological Analysis (IPA), research results will be obtained through a review of the patterns and final themes obtained. The results showed that the emergence of symbols was due to the unrest of corrupt government and defending the interested that was felt mutually by members of the Punk Community. This anxiety is generally conveyed through music, namely in song lyrics. In addition to music and songs, the symbols used by members of the punk community are conveyed in various forms such as black shirts, mohawck hair, boots, and other attributes. Each of these symbols has a collective meaning that members of the punk community themselves believe in. The collective meaning that members of the punk community widely believe has the meaning of resistance to a corrupt government. Furthermore, it was found that not only through songs, but punk ideology was also conveyed through fashion, attributes, and action. In the experience of using these symbols, receiving bad views from around is common for members of the punk community, including being scapegoats, difficult to gain trust from sponsors, being considered riotous, and so on. But this did not reduce the intensity of the use of symbols by members of the punk community despite being overwhelmed with mixed feelings of pride, happiness, and sadness. This feeling is based on a bad stigma and a pride for them to keep using their symbols and prove the opposite.